PKM KELOMPOK USAHA DODOL KABUPATEN BEKASI JAWA BARAT - Sari, Dessy Agustina; Hakiim, Azafilmi; Efelina, Vita; Asiah, Nurul; Sukanta, Sukanta (Universitas Esa Unggul, 2018)
AbstractDodol is a typical local food (snack heredity) and the making process applies the local community empowerment system. The initial treatment of raw materials to finished products runs manually (manpower) and production management has not been well ordered. This results in the selling price falling to third parties because the packaging segment is weak and the absence of packaging labels. The steps given to partners are the application of product distribution permit and business location permit, as well as post-dodol packaging tool technology cooled. The result of community service that has been running is the process of submitting SP-PIRT and SITU succeeded by the kelurahan - the implementing partner through the SKU before processing the document by the Bekasi District Health Office. Then, the implementation of 2 (two) pieces of equipment is completed to overcome the process of formation of the product - weighing and ending by the packaging in a vacuum. The goal is to save production time and overcome the adhesiveness of dodol, increase product shelf life due to vacuum sealed treatment, as well as make the product able to enter the food store or trip out of town. Aspects of increased production will also be examined for the solution provided. This is directed at improving daily production capacity and handling the number of workers when faced with orders on religious holidays.Ã‚Â Keywords: dodol, packaging, SITU, SP-PIRT7Ã‚Â AbstrakDodol merupakan makanan khas lokal (kudapan turun-temurun) dan proses pengerjaannya menerapkan sistem pemberdayaan masyarakat setempat. Perlakuan awal bahan baku hingga produk jadi berjalan manual (tenaga manusia) dan manajemen produksi belum tertata dengan baik. Hal ini mengakibatkan harga jual jatuh kepada pihak ketiga karena segmen pengemasan bersifat lemah dan tidak adanya penyematan label kemasan. Langkah-langkah yang diberikan kepada mitra adalah pengajuan izin edar produk dan izin lokasi usaha, serta teknologi alat pengemas pasca produk dodol didinginkan. Hasil pengabdian masyarakat yang telah berjalan adalah proses pengajuan SP-PIRT dan SITU disukseskan oleh pihak kelurahan Ã¢â‚¬â€œ mitra Ã¢â‚¬â€œ tim pelaksana melalui SKU sebelum pemrosesan dokumen oleh pihak Dinas Kesehatan kabupaten Bekasi. Lalu, pengimplementasian 2 (dua) buah peralatan tengah dirampungkan untuk mengatasi proses pembentukan wujud produk Ã¢â‚¬â€œ penimbangan dan diakhiri oleh pengemasan secara vakum. Tujuannya adalah penghematan waktu produksi dan penanggulangan sifat kelengketan yang dimiliki dodol, peningkatan umur simpan produk karena perlakuan vacuum sealed, serta menjadikan produk mampu memasuki pertokoan makanan maupun perjalanan ke luar kota. Aspek peningkatan produksi juga akan ditelaah atas solusi yang diberikan. Hal ini diarahkan kepada pembenahan kapasitas produksi harian dan penanganan jumlah pekerja bila menghadapi order pada hari besar agama.Ã‚Â Kata kunci :dodol, pengemasan, SITU, SP-PIRT7